Characterization of the S100A1 protein binding site on TRPC6 C-terminus - Bily, Jan; Grycova, Lenka; Holendova, Blanka; Jirku, Michaela; Janouskova, Hana; Bousova, Kristyna; Teisinger, Jan (PloS one, 2013)
The transient receptor potential (TRP) protein superfamily consists of seven major groups, among them the "canonical TRP" family. The TRPC proteins are calcium-permeable nonselective cation channels activated after the emptying of intracellular calcium stores and appear to be gated by various types of messengers. The TRPC6 channel has been shown to be expressed in various tissues and cells, where it modulates the calcium level in response to external signals. Calcium binding proteins such as Calmodulin or the family of S100A proteins are regulators of TRPC channels. Here we characterized the overlapping integrative binding site for S100A1 at the C-tail of TRPC6, which is also able to accomodate various ligands such as Calmodulin and phosphatidyl-inositol-(4,5)-bisphosphate. Several positively charged amino acid residues (Arg852, Lys856, Lys859, Arg860 and Arg864) were determined by fluorescence anisotropy measurements for their participation in the calcium-dependent binding of S100A1 to the C terminus of TRPC6. The triple mutation Arg852/Lys859/Arg860 exhibited significant disruption of the binding of S100A1 to TRPC6. This indicates a unique involvement of these three basic residues in the integrative overlapping binding site for S100A1 on the C tail of TRPC6.
Keywords: interakční proteinové domény a motivy; Protein Interaction Domains and Motifs; vazebná místa; sekvence aminokyselin; substituce aminokyselin; mutageneze cílená; vazba proteinů; TRPC6 Cation Channel; TRPC Cation Channels; Anisotropy; S100 Proteins; lidé; Molecular Sequence Data; Amino Acid Substitution; kationtové kanály TRPC; Amino Acid Sequence; vápník; Protein Binding; Mutagenesis, Site-Directed; molekulární sekvence - údaje; Protein Structure, Secondary; Calcium; Circular Dichroism; anizotropie; sekundární struktura proteinů; kationtový kanál TRPC6; proteiny S100; cirkulární dichroismus; Binding Sites; Humans